The role of extracellular vesicles in cellular senescence. (18th August 2022) - Estévez‐Souto, Valentín; Da Silva‐Álvarez, Sabela; Collado, Manuel
Abstract : Cellular senescence, an evolutionarily conserved mechanism that prevents the proliferation of damaged cells, is a very relevant cellular response involved in both physiological and pathological conditions. Even though senescent cells are stably growth arrested, they exhibit a complex and poorly understood secretory phenotype, known as senescence‐associated secretory phenotype, composed of soluble proteins and extracellular vesicles (EVs). Extracellular vesicles were initially described as a waste management mechanism to remove damaged components of cellular metabolism, but increasing evidence shows that EVs could also play important roles in intercellular communication. Recently, some studies showed that EVs could have fundamental functions during cellular senescence. Our purpose in this review is to clarify the increasing literature on the role of EVs in cellular senescence as key mediators in cell‐to‐cell communication. Abstract : Senescent cells are characterized by the acquisition a secretory phenotype known as SASP. Among the secreted factors, apart from soluble molecules, the relevance of extracellular vesicles (EVs) is increasingly recognized. EVs from senescent cells can exert different functions on recipient cells with biological consequences. Conversely, EVs from non‐senescent cells can modulate the senescence phenotype of target cells. These effects are mediated by the complex cargo on EVs.